2002
DOI: 10.1002/ijc.10423
|View full text |Cite
|
Sign up to set email alerts
|

Vasculogenic mimicry and pseudo‐comedo formation in breast cancer

Abstract: Tumors require a blood supply for growth and hematogenous metastases. Until recently, most research in this area has focused on the role of angiogenesis, the recruitment of new vessels into a tumor from preexisting vessels. Previously, in a study of breast cancer (IBC), in which we used estab-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
120
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(135 citation statements)
references
References 22 publications
10
120
3
Order By: Relevance
“…All these variables are important prognostic factors of PCa. This observation is different from that of a previous study in reference 20, that reported that breast carcinomas engaged in VM had a higher rate of distant metastasis, but there was no significant correlation between VM and lymph node metastasis. Another study on laryngeal squamous cell carcinoma reported a significant correlation between VM and lymph node metastasis status, but failed to find a significant correlation with distant metastasis.…”
Section: Discussioncontrasting
confidence: 99%
“…All these variables are important prognostic factors of PCa. This observation is different from that of a previous study in reference 20, that reported that breast carcinomas engaged in VM had a higher rate of distant metastasis, but there was no significant correlation between VM and lymph node metastasis. Another study on laryngeal squamous cell carcinoma reported a significant correlation between VM and lymph node metastasis status, but failed to find a significant correlation with distant metastasis.…”
Section: Discussioncontrasting
confidence: 99%
“…6,46 Human studies suggested that it furnishes an additional blood supply to the tumor and facilitates hematogenous dissemination. 12,37,46 In dogs this phenomenon was hypothesized to promote the lymphatic spread of tumor cells. 6 In the present study, we found vasculogenic mimicry almost exclusively in simple anaplastic carcinomas, which supports the theory that the formation of these channels is due to a lack of differentiation and marked plasticity of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…37,40 For CMCs, the histologic grade of malignancy is of prognostic significance, and many authors have suggested that it be routinely included in the pathology report. 21,26 There are several systems used to assign a histologic grade to CMCs; most are a modification of the method of Ellston and Ellis used for human breast cancers.…”
mentioning
confidence: 99%
“…4,5 Vasculogenic mimicry is another form of vessel formation that has been reported in certain tumor types, such as aggressive human uveal melanomas, prostate and breast tumors. [6][7][8] In these cases, networks of tumor cell-lined vascular channels were identified within the tumors. Finally, vessel co-option, implemented by tumor cells as a temporary means of gaining access to a blood supply, involves the tumor cells growing around and thus co-opting existing host vessels to form an initially well-vascularized tumor.…”
mentioning
confidence: 99%